Environmental Assessment of Healthcare Facilities in the Global South -- A Case Study from Pakistan - Ali, Mustafa; Cristiano, Silvio; Geng, Yong; Gonella, Francesco; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Pakistan is a resource-constrained country, poor in municipal and healthcare facilities. Existing healthcare structures in the country are often over-crowded, and an effective monitoring and assessment of their sustainability is therefore crucial. In this study, a systemic approach is outlined to evaluate the environmental sustainability of the largest and sole public hospital in the major city of Gujranwala, in the Punjab region of Pakistan. The Emergy (spelled with ``m'') Accounting (EMA) method is applied. Its operationalization allows to keep track of the amount of energy that was consumed in direct and indirect transformations to make a product or service. Relevant data include the hospital requirements in terms of energy, water, products, labor, and services. The EMA results offer a supply-side geobiosphere-oriented perspective. Emergy indicators show that the hospital is indirectly responsible for a significant stress on the environment, that might be decreased by an increased efficiency in the resource use. On the other hand, a hospital is a complex system, depending on skilled laborforce as well as on several fine imported medical products and related services, making it dependent on external socio-economic systems. The presented results address the geography dependent characteristics of the hospital, and can be used for benchmarking and future evaluation of similar hospitals within and across the region.